An Attribute-Based Encryption Scheme with Revocation for Fine-Grained Access Control in Wireless Body Area Networks. (11th November 2014) - Tian, Ye; Peng, Yanbin; Peng, Xinguang; Li, Hongbin
The wireless body area networks (WBANs) have emerged as a new method for e-healthcare. Without being measured face-to-face, the medical workers can give guidance to patients in a real-time way. WBANs can greatly improve the healthcare quality. The personal information and medical data are stored and processed in sensors. The security and privacy are two vital issues. In this paper, we design an attribute-based encryption scheme for fine-grained access control in WBANs. In our scheme, a user can decrypt a ciphertext if the attributes related with a ciphertext satisfy the user's access structure. The users can be revoked if necessary. Therefore, the security and privacy of patients can be protected. Our scheme provides confidentiality, security, and resistance to collusion attack. We analyze the correctness, security, and energy consumption of the scheme.